Da Síria a São Paulo: a vinda de famílias refugiadas sírias ao interior paulista - Cunha, Gabrielle da (2023)
This research aims to analyze the relationship between historical Syrian migration and the arrival of Syrian refugee families to Itapira, a city in the countryside of São Paulo, in order to understand the similarities and continuities in the migrant experience of a Syrian extended family that in 1945 had a relative who came to live in the country. After her, due to the impacts of the Syrian war, her brother and nephews came to take refuge in this same city, starting in 2011, and were also supported by her. Using ethnographic observation, statistical data and bibliographic references from Anthropology, Sociology, History and Demography on international migration and refuge in the state of São Paulo and Brazil, between 1880 and 2016, it was verified, from the trajectories of the interlocutors participating in the research, that the similarities and continuities in the integration process of refugee families are similar to those experienced by the aunt. In general, they are related to the difficulty of communication due to the language, the prejudiced view that the receiving society had towards them, but also the opportunities to live and have a dignified life in foreign territory after years established in Brazil. In addition, it also shows that migratory categories homogenize and frame refugees in a process that removes their identity, peculiarities and diverse possibilities and modes of existence that cooperate with the processes of invisibilization for the maintenance of social vulnerability and withdrawal of rights. In addition to adaptation, the trajectory of religious and conflict refugees is marked by memories of the violence they have suffered and in a way keeps them connected, or not, with their homeland.